2022
DOI: 10.3390/ijms23010530
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution and Functional Roles of miR408 and Its Targets in Plants

Abstract: MicroRNA408 (miR408) is an ancient and highly conserved miRNA, which is involved in the regulation of plant growth, development and stress response. However, previous research results on the evolution and functional roles of miR408 and its targets are relatively scattered, and there is a lack of a systematic comparison and comprehensive summary of the detailed evolutionary pathways and regulatory mechanisms of miR408 and its targets in plants. Here, we analyzed the evolutionary pathway of miR408 in plants, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 105 publications
(259 reference statements)
0
29
0
Order By: Relevance
“…In the low Cd-accumulation of wheat (Chuanyu 17), tae-miR-9,774 downregulated the expression between the group treated with 100 μM CdCl 2 and the control group ( Zhou et al, 2020 ). miR408, a conserved and ancient miRNA found widely in plants, is involved in photosynthesis and controls the target genes of copper-binding proteins ( Gao et al, 2022 ), which is vital for leaf growth. miR408 has been linked to drought and water shortage stress in A. thaliana , rice ( Roseeta et al, 2013 ; Sonia et al, 2017 ), wheat ( Guray et al, 2016 ), tomato ( Lycopersicon esculentum ; Bilgin et al, 2016 ), and perennial ryegrass ( Lolium perenne ; Nan et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the low Cd-accumulation of wheat (Chuanyu 17), tae-miR-9,774 downregulated the expression between the group treated with 100 μM CdCl 2 and the control group ( Zhou et al, 2020 ). miR408, a conserved and ancient miRNA found widely in plants, is involved in photosynthesis and controls the target genes of copper-binding proteins ( Gao et al, 2022 ), which is vital for leaf growth. miR408 has been linked to drought and water shortage stress in A. thaliana , rice ( Roseeta et al, 2013 ; Sonia et al, 2017 ), wheat ( Guray et al, 2016 ), tomato ( Lycopersicon esculentum ; Bilgin et al, 2016 ), and perennial ryegrass ( Lolium perenne ; Nan et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…miR408 has been linked to drought and water shortage stress in A. thaliana , rice ( Roseeta et al, 2013 ; Sonia et al, 2017 ), wheat ( Guray et al, 2016 ), tomato ( Lycopersicon esculentum ; Bilgin et al, 2016 ), and perennial ryegrass ( Lolium perenne ; Nan et al, 2020 ). The antioxidant capability of plants can be improved by miR408, which enhances cellular antioxidants ( Gao et al, 2022 ). In chickpea ( Cicer arietinum ), the expression of PLC (a target of miR408) decreased significantly with the overexpression of miR408 to provide drought tolerance ( Hajyzadeh et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, we intend to screen out genes closely related to nitrogen metabolism, and their target genes do not include key enzymes in nitrogen metabolism pathways, so we can consider studying from different directions. miR408 is involved in plant growth and stress response, and miR408 can regulate plastid cyanin (PC) by down-regulating target proteins, thereby affecting photosynthesis and ultimately promoting grain yield, revealing that miR408 plays an important role in regulating plant growth and development and plant responses to various abiotic and biotic stresses [29]. Previous studies have shown that overexpression of miR408 can signi cantly enhance the drought tolerance of chickpeas, while recent studies have shown that functional de cits of miR408 can negatively regulate light-dependent seed germination [30].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, studies have revealed that an array of miRNAs could be general regulators in the defense against stressful environments, such as miR408. miR408 is a highly conserved miRNA among plant species and responds to the availability of copper, and its target genes encode copper-containing proteins [ 14 ]. Furthermore, miR408 was found to be involved in various abiotic stress processes, including salinity, cold, oxidative stress, nutrient deficiency, and drought [ 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…miR408 is a highly conserved miRNA among plant species and responds to the availability of copper, and its target genes encode copper-containing proteins [ 14 ]. Furthermore, miR408 was found to be involved in various abiotic stress processes, including salinity, cold, oxidative stress, nutrient deficiency, and drought [ 14 , 15 , 16 ]. Although large-scale investigations have uncovered the essential functions of ncRNAs in annual plants in response to abiotic stress, related studies on how ncRNAs regulate forest trees under environmental stress are lacking.…”
Section: Introductionmentioning
confidence: 99%